1999
DOI: 10.1212/wnl.52.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Internal auditory artery infarction

Abstract: The partial sparing of the inferior vestibular labyrinth may indicate a decreased vulnerability to ischemia because of its better collateral blood supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 28 publications
2
113
0
1
Order By: Relevance
“…It has been widely postulated that interruption of the cochlear blood flow causes sudden sensorineural hearing loss. [1][2][3] The introduction of an adenovirus inoculation technique for ear treatment may prove very beneficial for saving useful hearing after sudden deafness. In clinical use, however, the Ad-GDNF treatment would be given after the onset of sudden deafness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely postulated that interruption of the cochlear blood flow causes sudden sensorineural hearing loss. [1][2][3] The introduction of an adenovirus inoculation technique for ear treatment may prove very beneficial for saving useful hearing after sudden deafness. In clinical use, however, the Ad-GDNF treatment would be given after the onset of sudden deafness.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, the details of the effects of transient ischemia on the cochlea remain unclear. Using a technique called experimental hindbrain ischemia, 4 we successfully made a chronic animal model of transient cochlear ischemia in Mongolian gerbils and demonstrated that inner ear damage was closely related to the progressive inner hair cell (IHC) loss that follows ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…3,[20][21][22] The superior labyrinth supplied by the anterior labyrinthine artery is vulnerable to ischemia because of its small caliber and the lack of collaterals. 35 Relative sparing of the inferior vestibular labyrinth in a patient with isolated internal auditory artery infarction provides a clinical support for this explanation. 35 The prominent downbeat component of the induced nystagmus was ascribed to bilateral, but asymmetrical excitation of the anterior and horizontal semicircular canals in both sides.…”
Section: Strokementioning
confidence: 93%
“…Periods of confusion, elevated serum lactic acid levels around times of attacks, strokelike spells, magnetic resonance imaging (MRI) white matter signal changes, migrainelike headaches, seizures, diabetes, mitochondrial gene mutation (Mt-RNR1, Mt-TS1, POLG genes) 222,223 Other mitochondrial disorders Variable phenotypes 224 Bilateral synchronous internal auditory artery occlusion associated with vertebrobasilar vascular disease Vertigo, dysarthria, facial weakness, ataxia, nystagmus, unilateral numbness, abnormal computed tomography or magnetic resonance angiogram of the vertebrobasilar vasculature 48,50,[225][226][227] Cogan syndrome Nonsyphilitic interstitial keratitis of the cornea, hearing loss, vertigo 40 Neoplastic (neurofibromatosis II, bilateral vestibular schwannomas, intravascular lymphomatosis, others) Abnormal brain MRI or cerebrovascular imaging study [228][229][230] Sarcoidosis Pulmonary symptoms, bilateral vestibular loss, elevated serum angiotensin-converting enzyme level or abnormal Gallium scan 231,232 Hyperviscosity syndrome Mucous membrane bleeding, neurologic and pulmonary symptoms, associated retinopathy 233 carcinomatous meningitis, lymphomatous meningitis, and, very rarely, central nervous system (CNS) intravascular lymphomatosis and migrainous infarction. 59 Features that suggest multiple sclerosis would be unilateral weakness or numbness, visual loss, diplopia, or paraparesis.…”
Section: Table 5 Checklist Of Features Often Associated With Specifimentioning
confidence: 99%